Review of policies encouraging renewable energy integration & best practices. (May 2015) - Abdmouleh, Zeineb; Alammari, Rashid A.M.; Gastli, Adel
Abstract: This article provides policy-makers and renewable energy project developers with background information and analysis into the successful penetration of renewable energy policies. The analysis emphasizes on the different mechanisms to establish an encouraging regulatory framework for renewable energies and examines examples of both successful and failed experiences, through case studies and analysis of various countries. This analytic survey attempts to shed light on the factors which led to successful implementation of renewable energy depending not only on different countries experience, but also on the different sources and technologies for renewable electricity. The main objectives through the provision of this overview are to help policy implementers learn from each other׳s experiences and contribute to the efforts to meet indicative renewable energy targets. The methodology applied in this document is to collect all applied mechanisms helping deploying renewable energy projects with a reviewing of study cases analysis for some specific experiences. Then the information are classified and discussed from the financial, fiscal, legislative, political, technological and environmental points of view in order to make it a reference and a guideline for other renewable energy policies studies.